Complications of twin pregnancies in a teaching hospital - Ramos, José Geraldo (2022)
OBJECTIVE: To compare maternal risk factors, types of twins, and complications of twin pregnancies.MATERIALS AND METHODS: We carried out a retrospective study of twin pregnancies born at the Hospital de Clínicas de Porto Alegre and with gestational age from 20 weeks to term. We assessed data regarding 323 twin pregnancies concerning maternal, gestational, labor, and neonatal characteristics.RESULTS: Our patients presented an age average of 27.5 years and 106 were nulliparas (32.8%). Babies were born after an average 35.3 weeks of pregnancy term. Prematurity was the most important complication, with 138 cases of preterm births (42.7 %) and 98 cases of preterm labor (30.3%). Complications occurred most frequently when the maternal age was less than 35 years old (P = 0.01) and the gestational age was less than 32 weeks (P = 0.002). Presentation of the fetuses were distributed in 176 cases of cephalic/cephalic, 101 cases of cephalic/pelvic, 23 cases of pelvic/pelvic, among others.CONCLUSIONS: Prematurity was the most frequent complication found in twin pregnancies. Maternal age of less than 35 years and gestational age of less than 32 weeks were factors for twin pregnancies at risk for complications.